The M/G/oo queue busy period length exponential behavior for particular service times distributions collection - Ferreira, M. A. M. (2016)
The aim of this work is to look for exponential behavior conditions for the M/G/oo queue busy period length distribution, in the case at which a particular service time's collection is considered.